Long-Term Outcomes for Out-of-Hospital Cardiac Arrest in Elderly Patients: An Analysis of Cardiac Arrest Registry to Enhance Survival Data Linked to Medicare Files. Issue 10 (4th October 2022) - Chan, Paul S.; McNally, Bryan; Chang, Anping; Girotra, Saket; Al-Araji, Rabab; Mawani, Minaz; Ahn, Ki Ok; Merritt, Robert
Abstract : Background: Most studies on out-of-hospital cardiac arrest have primarily focused on in-hospital or short-term survival. Little is known about long-term outcomes and resource use among survivors of out-of-hospital cardiac arrest. Methods: In this observationsl study, we describe overall long-term outcomes for patients from the national Cardiac Arrest Registry to Enhance Survival linked to Medicare files to create the Cardiac Arrest Registry to Enhance Survival: Mortality, Events, and Costs for Cardiac Arrest survivors dataset. Cardiac Arrest Registry to Enhance Survival data between 2013 and 2019 were linked to Medicare data using probabilistic matching algorithms. Overall long-term mortality, readmissions, and index hospitalization costs are reported for the overall cohort. Results: Among 56 425 patients who were 65 years of age or older in Cardiac Arrest Registry to Enhance Survival who survived to hospital admission, 26 875 (47.6%) were successfully linked to Medicare files. Mean ( + SD) cost of the index hospitalization was 23 262 + 24 199 and the median cost was 14 636 (interquartile range, 9930–30 033). Overall, 8676 (32.3%) survived to hospital discharge with 38.0% discharged home, 11.8% to hospice care, and the remaining 50.2% to other inpatient, skilled nursing care, or rehabilitation facilities. Mortality after discharge was initially high (27.0% at 3 months) and then increased gradually, with 1- and 3-year mortality of 37.1% and 50.1%, respectively. During the first year, 40.1% were readmitted at least once, with 19.7% readmitted on > 1 occasion. Conclusions: The Cardiac Arrest Registry to Enhance Survival: Mortality, Events, and Costs for Cardiac Arrest survivors registry includes rich data on postdischarge outcomes and resource utilization. Use of this dataset will enable future investigations on the long-term effectiveness, costs, and cost-effectiveness of various interventions for out-of-hospital cardiac arrest in elderly patients.